Deciphering Structural Fingerprints for Hexafluorobenzene with Density Functional Theory - Raja, G.; Saravanan, K.; Sivakumar, S. (Asian Journal of Chemistry, 2013)
This work deals with the vibrational spectroscopy of hexafluorobenzene by means of quantum chemical calculations. The FTIR and FT-Raman spectra were measured in the condensed state. The fundamental vibrational frequencies and intensity of vibrational bands were evaluated using density functional theory (DFT) with the standard B3LYP/6-311+G** basis set combinations and was scaled using various scale factors which yields a good agreement between observed and calculated frequencies. The vibrational spectra were interpreted with the aid of normal coordinate analysis based on scaled quantum mechanical force field. The results of the calculations were applied to simulated infrared and Raman spectra of the hexafluorobenzene, which showed excellent agreement with the observed spectra.